1961
DOI: 10.1021/jo01067a642
|View full text |Cite
|
Sign up to set email alerts
|

Notes- Acetals and Ketals of 1,3-Diols

Abstract: In no case did we obtain a product melting as low as -20°. The solutions for infrared work were obtained by dissolving the freshly prepared crystalline -hydroxyethyl peracetate in cold chloroform.Infrared spectra. A Baird-Atomic infrared spectrophotometer Model 4-55 was used in this work. The chloroform solution of peroxide was introduced immediately after preparation into the previously cooled low-temperature cell10 at 0°. A variable-path length cell was used in the reference beam to compensate for the chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(2) is quite insoluble in almost all organic solvents, such as benzene. Conrad et aL (24) found that the reaction of aldehydes with 2 in benzene gave diacetals as the only products. Although 2 is quite soluble in diethylene glycol diethyl ether at its boiling point, the condensation reaction was slow, and a pure product was not isolated.…”
Section: Resultsmentioning
confidence: 99%
“…(2) is quite insoluble in almost all organic solvents, such as benzene. Conrad et aL (24) found that the reaction of aldehydes with 2 in benzene gave diacetals as the only products. Although 2 is quite soluble in diethylene glycol diethyl ether at its boiling point, the condensation reaction was slow, and a pure product was not isolated.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hudson's results, the acetalization of xylitol with 37% aqueous formaldehyde can be efficiently carried out in the presence of hydrochloric acid, but the major product was the diacetal, which was obtained in 91% yield . The monoacetal from formaldehyde was obtained from the acid hydrolysis of the diacetal . Julnes reported the monoacetal could be obtained in 41.6% yield using xylitol and n ‐butanal in the presence of hydrochloric acid, but the n ‐butanal conversion and the monoacetal selectivity were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The monoacetal from formaldehyde was obtained from the acid hydrolysis of the diacetal. [17,18] Julnes [19] reported the monoacetal could be obtained in 41.6% yield using xylitol and n-butanal in the presence of hydrochloric acid, but the n-butanal conversion and the monoacetal selectivity were not reported. The outcome using n-butanal was different to formaldehyde because of the larger amount of water (0.5 mol of reactant dissolved in 300 mL of water) used in the n-butanal reaction that was required for all of the reactants and products to be dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with the ketalization of pentaerythritol, numerous diketals have been reported. 10,11 However, an examination of the literature for the preparation of monoketals revealed that only few efforts have been made to obtain these synthetic intermediates, since Böeseken, 12 Orthner and Freyss, 13 and Orthner 14 published pioneer works regarding it. The extreme polarity of pentaerythritol and consequently its insolubility in almost all organic solvents appear to be the main difficulties found when dealing with the studies concerning the preparation of monoketals.…”
mentioning
confidence: 99%
“…All available methods give low yields of monoketals. Conrad et al 10 have reported the preparation of monoketals from diketals by partial hydrolysis obtaining the monoketal of pentaerythritol and cyclohexanone in 12% yield. Schneider et al 11 have described methods for preparation of the mono and diketals of pentaerythritol in benzene-dioxane (1:1) as solvent, but neither yields nor selectivities towards both ketalization products have been reported.…”
mentioning
confidence: 99%